Audio Watermarking Scheme Robust against Desynchronization Based on the Dyadic Wavelet Transform. (2nd March 2010) - Wang Wang, Yong Yong; Wu Wu, Shaoquan Shaoquan; Huang Huang, Jiwu Jiwu
Abstract : Digital watermarking is a technique used to embed an extra piece of information into multimedia signals without degrading the signal quality. For robust audio watermarking, geometrical modifications are common operations and present many challenges because they severely alter the tempo or spectral structures of the audio and thus cause watermark desynchronization. However, most of the existing audio watermarking algorithms lack resynchronization ability due to the nongeometrically-invariant nature of the watermarking domain. In this paper, we consider the dyadic wavelet transform (DYWT) for its geometrical invariants which can help resynchronize the watermark. We then design a novel embedding method based on shape modulation which is demonstrated to be robust against many kinds of attack. Based on the knowledge of the insertion, deletion, and substitution (IDS) channel, we carefully design a novel error correction coding (ECC) with the ability of bit-resynchronization to correct the IDS errors in the watermark. Compared with existing algorithms, our algorithm achieves greater robustness to geometrical modifications and other common operations.